The Swift and Secret Messenger: John Wilkins’s Mercury and the Paradoxes of Language - Łączyńska, Klaudia (Studia Anglica Posnaniensia, 2016)
John Wilkins’s Mercury or the Secret and Swift Messenger: Showing How a Man May with Privacy and Speed Communicate His Thoughts to a Friend at Any Distance was first published in 1641. As a book on cryptography presenting a variety of secret means of communication at a distance it seems to have appeared at just the right time, when the biblical curse of the confusion of tongues was doubled by the curse of political confusion on the brink of the English civil war. However, the book seems to be more than just a detailed account of methods of secret writing; its topic gives the author a chance to present his views on language which he would later develop in his life’s work An Essay towards Real Character and a Philosophical Language published in 1668. The Essay had received much greater critical attention than the early pamphlet, which is usually referred to as merely a prelude to an account of his universal language project. Indeed, in the little book on cryptography, Wilkins already demonstrated his awareness of the conventional character of language and its role within the system of human interactions, as well as advertised a project of philosophical language that would enhance communication between all nations and remedy the curse of Babel. The aim of this paper is to demonstrate that the value of the pamphlet lies also in the insight that it gives into the seventeenth-century debates on the nature of language and into arguments which were often provided, in equal measure, by theology, Hermetic lore, mythology, literature and early modern science. Wilkins’s meticulous recording of the contradictory views and propositions on language produces a sense of methodological inconsistency that leads to ambiguities and paradoxes. However, in the medley of concepts and the collection of linguistic “curiosities” that Mercury presents, a careful reader will discern the growing mistrust of language as a means of representing reality and as a foundation of knowledge, which was one of the symptoms of the general crisis of representation leading to an epistemological shift that started in the seventeenth century.